DEVELOPMENT OF A TRADITIONAL CHILDREN GAME BASED INSTRUCTIONAL MODEL TO OPTIMIZE KINDERGARTENERS’ FUNDAMENTAL MOTOR SKILL - Wawan Sundawan Suherman; Dapan Dapan; Guntur Guntur; Nur Rohmah Muktiani (LPMPP Universitas Negeri Yogyakarta, 2019)
Traditional children game is proposed as a suitable physical activity for instructional mean in kindergarten. The research intends to develop traditional children game based instructional model to optimize development of fundamental motor skills of kindergarteners. This research and development used an approach from Borg Gall. The research involved kindergartens in Yogyakarta, Indonesia. Data were collected by interview, observation, and documentation, and then were analyzed in three steps: organization and reduction, displaying, and summarization and verification. The study phase follows activities: identification of theoretical basis and determination of instructional model design, identification and analysis of traditional children game, and validation of instructional model. After being validated by material experts and teaching experts, the traditional children game based instructional model for optimizing the development of kindergarteners’ fundamental motor skills consists of: (1) concepts/theoretical basis, (2) activity stages, (3) social systems, (4) principles of reaction, (5) supporting system, and (6) model impact.